2005
DOI: 10.1007/bf02973875
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of arthritic inflammation using an oriental herbal combination BDX-1 isolated fromAchyranthes bidentata andAtractylodes japonica

Abstract: An oriental herbal combination (BDX-1) was isolated from Achyranthes bidentata and Atractylodes japonica. We previously tested the clinical effectiveness of BDX-1 in rheumatoid arthritis (RA) patients and found that it has a beneficial therapeutic effect. Here, we provide experimental evidence for the effectiveness of BDX-1 on RA in murine models. The oral administration of BDX-1 was found to markedly inhibit collagen-induced arthritis, adjuvant-induced arthritis, and zymosan-induced inflammation. It also inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Moreover, all SMF four ingredients contain the anti-inflammatory substances, such as berberine and atractylodine, which were confirmed to have anti-inflammatory activity. [50][51][52][53] Thus, we deduce that SMF inhibits inflammation response in OA by interfering with secretion of pro-inflammatory cytokines and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, all SMF four ingredients contain the anti-inflammatory substances, such as berberine and atractylodine, which were confirmed to have anti-inflammatory activity. [50][51][52][53] Thus, we deduce that SMF inhibits inflammation response in OA by interfering with secretion of pro-inflammatory cytokines and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 79%
“…the treatment of many infl ammatory diseases including atherosclerosis (Han et al, 2005). To fi nd new therapeutic agents for vascular infl ammation in atherosclerosis, we examined several original herbs and found that treatment with EGJ can signifi cantly attenuate monocyte adhesion to TNF-α-stimulated HUVEC by inhibiting the expression of VCAM-1 and E-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated supernatants were mixed with an equal volume of Griess reagent and then incubated at room temperature for 10 min. Nitrite production was determined by measuring absorbance at 540 nm versus a NaNO 2 -derived standard curve (Han et al, 2005a). Immature DCs (iDC) recovered from these cultures on day 8 were generally >85% CD11c + , but not CD3 + and B220 + .…”
Section: Generation Of Primary Macrophages and Dendritic Cellsmentioning
confidence: 99%